FAKTOR PERGESERAN SISTEM PEWARISAN HARTA PENCARIAN DI KURAITAJI KECAMATAN PARIAMAN SELATAN SUMATERA BARAT - DESY UTAMI NINGSIH (PREMISE LAW JURNAL, 2016)
Minangkabau is one of the places where the people are adhered to matrilineal system (maternal line), from the small circle of life, family life, and the highest level of life which is called “nagari” It can be seen that “maternal line of descent” is the factor which organizes the community although in the nagari there is other adhesive factors. The organized life according to maternal line in daily life is called as the life according to adat. The factor of the shift in the system of joint property inheritance at Kuraitaji, Pariaman Selatan Subdistrict, West Sumatera, brought about some problems of the research as follows: first, how about the scope of joint property in Minangkabau; secondly, how about the implementation of the distribution of joint property at Kuraitaji, Pariaman Selatan Subdsistrict; and thirdly, what factors which caused the shift in the implementation of distributing joint property inheritance at Kuraitaji, Pariaman Selatan Subdistrict, West Sumatera. Keywords :      Shift Factors, Inheritance, Joint Property